Emergence of Drug Resistance in Human Immunodeficiency Virus Type 1 Infected Patients from Pune, India, at the End of 12 Months of First Line Antiretroviral Therapy Initiation. (10th April 2014) - Patil, Rajesh T.; Gupta, Rajiv M.; Sen, Sourav; Tripathy, Srikanth P.; Chaturbhuj, Devidas N.; Hingankar, Nitin K.; Paranjape, Ramesh S.
Abstract : Introduction . In India, 4, 86, 173 HIV infected patients are on first line antiretroviral therapy (ART) as of January 2012. HIV drug resistance (HIVDR) is drug and regimen-specific and should be balanced against the benefits of providing a given ART regimen. Material & Methods. The emergence of HIVDR mutations in a cohort of 100 consecutive HIV-1 infected individuals attending ART centre, on first line ART for 12 months, was studied. CD4 + T-cell counts and plasma HIV-1 RNA level were determined. Result. Out of the 100 HIV-1 infected individuals, 81 showed HIVDR prevention (HIV-1 RNA level < 1000/mL), while the remaining 19 had HIV-1 viral RNA level > 1000/mL. HIVDR genotyping was carried out for individuals with evidence of virologic failure (HIV-1 RNA level > 1000/mL). The most frequent NRTI-associated mutation observed was M184V, while K103N/S was the commonest mutation at NNRTI resistance position. Conclusion . Our study has revealed the emergence of HIVDR in HIV-1 infected patients at the end of 12 months of first line ART initiation. For NRTIs, the prevalence of HIVDR mutations was 9% and 10% for NNRTIs. Our findings will contribute information in evidence-based decision making with reference to first and second line ART delivery and prevention of HIVDR emergence.